Mûnis ve Âgehî Firdevsü’L-İkbâl (vr.1b-156b) (Giriş, İnceleme, Metin, Dizin) - Kahya, Hayrullah (My University, 2010)
Çağatayca, Türk dilinin Orta Asya’da 15.-20. yüzyılları arasındaki dönemine verilen addır. Bu tarihî Türk lehçesinin ilk dönemi ve Nevaî ile gelişen klâsik dönemi hakkında epeyce araştırma ve çalışma yapılmıştır. Ancak son devri hakkında yapılan çalışmalar azdır. Bu çalışmada Çağataycanın son devirlerine ait Firdevsü’l-ikbâl adlı bir tarih kitabı incelenmiştir. Bu kitap Mûnis Harezmî ve onun hem yeğeni hem de talebesi olan Âgehî tarafından 19. yüzyılın ilk yarısında yazılmıştır. Rusların Orta Asya’yı işgalinin hemen öncesine kadar Orta Asya, özellikle Hive Hanlığı tarihini anlatan yerli bir kaynak olarak Firdevsü’l-ikbâl, hem dili hem de konusu bakımından önemlidir. Elinizdeki çalışma, Firdevsü’l-ikbâl’in 1b-156b varakları arasındaki bölümü üzerinde yapılmıştır. Çalışmada Çağatay edebiyatı ve belli başlı temsilcileri ile eserin içeriği hakkında bilgi verildikten sonra metnin imlâ ve dil özellikleri üzerinde durulmuştur. Metnin transkripsiyonu yapılmış, en sonunda da dizinine yer verilmiştir. Bu çalışma sayesinde Orta Asya Türk tarihinin 18.-19. yüzyılları hakkındaki bilgilerimiz artmış, son dönem Çağataycasının dili ve kelime hazinesi hakkındaki araştırmalara da katkıda bulunulmuş olmaktadır. atayca, Firdevsü’l-ikbâl, Türk dili, Orta Asya Türk tarihi, Mûnis ve Âgehî

Chagatay language is the name of the age between 15th-20th centuries in which Turkish language was used in Central Asia. Many researches and studies have been done about the first period of this Turkish dialect and classic period which was developed by Nevai. However, studies about the last period of Cagatay language have decreased recently. In this study, a history book called Firdevsü’l-ikbâl which belongs to last periods of Chagatay language was examined. This book was written at the beginning of the 19th century by Mûnis Harezmî and both his nephew and his student Âgehî. Firdevsü’l-ikbâl which is a local book that narrates the history of Khive Khanete and Central Asia before Russian occupation is important because of both its language and theme. This study has been done on the part of 1b-156b sheets of the book. At first, some information is given about Chagatay literature and its main characters and then the content of the book. Characteristics of spelling and language are mentioned in the research part. Transcription of the text was done and there is an index at the end. Thanks to this study, we have more information about Central Asia Turkish History in 18th-19th century and also a contribution has been done to the last period of Chagatay language and its vocabulary. Key words : Chagatay language, Firdevsü’l-ikbâl, Turkish language, History of Turks in Middle Asia, Mûnis and Âgehî
Keywords: Türk Dili